2005
DOI: 10.1084/jem.20041385
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mobilization of murine and human hematopoietic stem and progenitor cells with AMD3100, a CXCR4 antagonist

Abstract: Improving approaches for hematopoietic stem cell (HSC) and hematopoietic progenitor cell (HPC) mobilization is clinically important because increased numbers of these cells are needed for enhanced transplantation. Chemokine stromal cell derived factor-1 (also known as CXCL12) is believed to be involved in retention of HSCs and HPCs in bone marrow. AMD3100, a selective antagonist of CXCL12 that binds to its receptor, CXCR4, was evaluated in murine and human systems for mobilizing capacity, alone and in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
918
0
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,012 publications
(987 citation statements)
references
References 53 publications
45
918
0
16
Order By: Relevance
“…24 At this peak, the number of circulating colony-forming cells increased 16-fold ( Figure 1a). Bone histomorphometry revealed that unlike G-CSF or CYP, AMD3100 did not alter osteoblasts or osteoid surfaces on trabecular or endocortical bone of the metaphysis (Figures 1 b --e).…”
Section: Effect Of G-csf Cyp and Amd3100 On Osteoblasts And Bone Formentioning
confidence: 98%
See 1 more Smart Citation
“…24 At this peak, the number of circulating colony-forming cells increased 16-fold ( Figure 1a). Bone histomorphometry revealed that unlike G-CSF or CYP, AMD3100 did not alter osteoblasts or osteoid surfaces on trabecular or endocortical bone of the metaphysis (Figures 1 b --e).…”
Section: Effect Of G-csf Cyp and Amd3100 On Osteoblasts And Bone Formentioning
confidence: 98%
“…However, whether CYP shuts down HSC niches in mouse strains such as C57BL/6 with low protease release has not been investigated. AMD3100 has been reported to mobilize HSC by directly antagonizing the CXCR4-mediated sensing of the CXCL12 chemotactic gradient in the BM that retains HSPC within this tissue, 24,25 and by promoting the release of CXCL12 from BM stromal cells into the circulation, thereby disrupting the CXCL12 gradient that retains HSC within the BM. 26 These latter findings suggest that AMD3100 may also alter HSC niches.…”
Section: Introductionmentioning
confidence: 99%
“…The laminin receptor has 7 npg also been shown to play a key role in cancer metastasis [87]. Similarly, stromal cell derived factor and its receptor CXCR4 form a critical regulatory axis for HSC migration, engraftment and homing [88][89][90][91][92], and also function in the metastasis of breast, prostate and other types of cancer [73,[93][94][95][96][97][98][99][100]. Matrix metalloproteinase-9 (MMP-9), belongs to a family of MMPs that plays a critical role during cancer cell invasion [101][102][103][104], and it is also involved in HSC homing and migration [105][106][107].…”
Section: Stem Cell Niche and Tumor Migrationmentioning
confidence: 99%
“…The concentration of soluble SDF-1 in the blood, however, increases in association with many of the conditions that induce stem/progenitor cell mobilization. Both sustained elevations of SDF-1 in NOD/SCID mice delivered by an adenoviral vector delivery system [34][35][36] , and chronic administration to the animals of SDF-1 peptide analogs 37,38 , result in mobilization of stem/ progenitor cells. In addition, increased plasma SDF-1 levels are also observed during mobilization induced by sulfated glycans 39 .…”
Section: Introductionmentioning
confidence: 99%